O metodzie korekty prognoz minimalizującej koszt niezbilansowania zapotrzebowania na energię elektryczną - Wójciak, Mirosław; Wójcicka, Aleksandra (The Method of Forecast Correction Minimizing the Cost of Non-Balanced Electric Power Demand, 2006)
From 1st July 2002 twenty-four-hour balancing energy demand market/system implemented specific system of clearing prices. The prices demonstrate significant asymmetry . This way each deviation/difference of demand and forecast is a measurable loss which mostly depends on the direction of the difference. Because of the specific asymmetry it is better to overcontract (forecasts higher than the demands - long position) and to sell the surplus if it occurs. To minimise the costs of balancing the difference the forecast of two presented models was adjusted by multiplying it by ratio к which was upgraded together with models' parameters. Correction is set to minimise the function of cost balancing which leads to lowering the functioning costs of distributing company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 336-347